A FORGOTTEN THEORETICAL CONNECTION OF AL-GHAZĀLĪ’S CLASSIFICATION OF RELIGIOUS SCIENCES: A CRITICAL ANALYSIS - Islam, Tazul; Zulkifli, M. Y. (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
Each classification of science propounded by al-Ghazālī is generally based on a specific theoretical background. For religious science, which is relatively more focused in his discussion, he ascribed the entire discourse to a theory called “lubāb al-Qur’an” (essence of the Qur’an). This particular theory was born in another concept he calls ‘maqāsid al-Qur’an’ (objectives of the Qur’an) which is increasingly fashionable in contemporary Islamic scholarship. Despite this attention from scholars, the concerned discussion in previous literatures seems more interested in outlining the branches religious science that are enumerated by Al-Ghazālī rather than in digging deep into the above-mentioned background theory. In this milieu, the existing gap of study provokes exploring this very theoretical basis and its implications. Hence, to explore various dimensions of this gap and to shed light on it, this research aims at exploring critically the conceptual background of al-Ghazālī’s classification of religious sciences. It is hoped that this study may lay a new direction for this emerging debate.